Uma análise da variação do efeito preço na função de demanda residencial por água para diferentes níveis de consumo - Gomes, Camila Rocha (2020)
This paper aims to estimatea residencial water demand function to the State of Goiás, considering the probable variations of the price effect at the different levels of consumption. The analysis is based on the assumption that users with greater amount consumed are less sensitive to the price variotions. For this purpose, the quantile regression technique is used in a unbalanced panel data of monthly water consumption for each neighborhood served by Saneago. The results show that consumers with a lower volume consumed have a higher price effect than those that demand a larger amount of water, confirmingthe basic hypothesis of the study. Given this variability, it is possible to affirm that only the tarif policy used by Saneago, IBP, does not promote the rational use and is not efficient in the universalization of water supply. Since, by increasing the price, the decrease will occur in those locations that by nature consume less and, usually, for subsistence purposes.